Pengaruh Content Marketing, Social Media Marketing, dan Viral Marketing Terhadap Keputusan Pembelian Konsumen: Studi Kasus pada Cenklik Coffee - Sera Triya Meilida; Cindy Agnesia; Balqis Larasati; Septia Nur Humairoh; Nadiya Fikriatuz Zakiyah (Pusat Riset dan Inovasi Nasional, 2025)
The development of digital technology has brought significant changes in marketing strategies, including in the culinary industry such as coffee shops. This study aims to determine the effect of content marketing, social media marketing, and viral marketing on consumer purchasing decisions, with a case study on Cenklik Coffee. This study uses a qualitative approach with a case study method and data collection techniques through literature review. The results of this study are expected to provide a deeper understanding of the effectiveness of each digital marketing strategy in influencing consumer purchasing decisions. The findings of this study can be used by business actors, especially in the coffee shop sector, to design more effective and attractive digital marketing communication strategies. Data validity is guaranteed through triangulation from various sources such as Google Maps reviews and Cenklik Coffee social media content analysis. This study provides a practical contribution to business managers as well as a theoretical basis for further research in the fields of consumer behavior and digital marketing.